Pengembangan video animasi materi bangun datar berbasis budaya Melayu di sekolah dasar - Nindy Aisyah; Jesi Alexander Alim; Mahmud Alpusari (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2022)
This study aims to develop an animation video of flat shapes based on Malay culture in elementary schools that meet valid and practical criteria. This method used is research and development with the Plomp model. The development phase is carried out in 3 phases: preliminary research phase, prototyping phase, and assessment phase. Animated video development products are validated by content, media, and linguistic experts. While the practicality of the product made is seen from the responses of teachers and students, and the data are obtained by observation, interviews, and questionnaires. Data processing is carried out by means of quantitative and qualitative analysis. The animated video developed by the researchers meets the valid and practical criteria and can be used in learning flat shapes in elementary schools.